Mindfulness and related factors among addicted adolescents - Uzun, Mehmet Erdem; Uslu, Hüseyin; Kılınçel, Şenay; Uzunok, Barış; Korkmaz, Muhammet Furkan; Şirin, Hande (The European Research Journal, 2021)
Objectives: Mindfulness has been defined as “the clear and single-minded awareness of what happens to us and in us, at the successive moments of perception”. Mindfulness-based therapies have been used in the treatment of psychiatric diseases in recent years. There is no study on the mindfulness of addicted adolescents in our country. In this study, we aimed to determine the level of the mindfulness and the factors affecting the mindfulness among addicted adolescents. Methods: Fourty drug-addicted adolescents and fourty five healthy adolescents were included in the study. Sociodemographic Data Form, Addiction Profile Index Adolescent Form (BAPI-E), Mindful Attention Awareness Scale (MAAS), Coping Orientation to Problems Experienced (COPE), Metacognition Questionnaire for Children and Adolescents (MCQ-C) and Child-Adolescent Social Support Scale (CASS) were applied to the participants. Clinical interviews (based on DSM-V) were performed to assess addiction. Results: There were no significant differences in the mindfulness levels between the addicted and the non-addicted groups. The mindfulness levels of the patients who attempted suicide were lower than the patients who did not attempt suicide. Behavioral disengagement sub-scales of COPE were significantly higher in the substance use and the denial group. Conclusions: Non-functional styles coping with stress were found to be significantly higher in the addicted group, however, we found no significant differences in the mindfulness levels.